The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.18844/cjes.v11i4.4057
|View full text |Cite
|
Sign up to set email alerts
|

Integration of engineering design in early education: How to achieve it

Abstract: Young boys and girls make houses and beds from cloths and cartons for their dolls, erect shelters and fences for toy animals, build ramps and garages from blocks for toy cars, and lift objects using a rope and reel for having fun. Thanks to their experiences with such design-based games, children combine science with engineering and try to understand and explain the facts and happenings around them with their own information and explanations. In recent years, the literature heavily provided marked evidence tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 0 publications
0
8
0
2
Order By: Relevance
“…Dilek et al (2020) indicated that reading and engaging with picture storybooks promoted interest in STEAM topics and modelling and reinforced appropriate vocabulary usage. Cinar (2019) concludes that young children without writing and reading capabilities benefit from this form of narrative-based and visual introduction.…”
Section: Significance Of Integrating Steam Education In Ecementioning
confidence: 98%
See 4 more Smart Citations
“…Dilek et al (2020) indicated that reading and engaging with picture storybooks promoted interest in STEAM topics and modelling and reinforced appropriate vocabulary usage. Cinar (2019) concludes that young children without writing and reading capabilities benefit from this form of narrative-based and visual introduction.…”
Section: Significance Of Integrating Steam Education In Ecementioning
confidence: 98%
“…12 papers aimed to provide a definition towards understanding integrating STEAM in ECE. Cinar (2019), Hassan et al (2019), Lin et al (2021), andTank et al (2018) had a STEAM definition that has the integration notion embedded. Interestingly, Smith and Cline (2016) focused on defining STEAM integration while Aldemir and Kermani (2017), Kermani and Aldemir (2015), and Lowrie and Larkin (2020) define integrating STEAM from an ICT focus that positions ICT as a tool to explore STEAM at different integration levels.…”
Section: Defining Integrating Steam In Ecementioning
confidence: 99%
See 3 more Smart Citations